Factors Influencing the Purchase Intention of Generation Z Muslim Consumers Towards Halal and Environmentally Friendly Local Cosmetic Products - Dita Ristiyana; Soepatini Soepatini; Moechammad Nasir (Universitas KH. Abdul Chalim Mojokerto, 2025)
The aim of this research is to determine the factors that influence the purchase intention of generation Z Muslim consumers towards local cosmetic products that are halal and environmentally friendly. This research uses a quantitative method in the form of a questionnaire, the sampling technique is non-probability sampling with a purposive sampling method. The population in this study is generation Z who live in the Greater Solo area and have never used Avoskin products. The sample in this study was 312 respondents. The data analysis technique used in this research is the SEM PLS method using SmartPLS software. Based on this research, it was found that of the 23 hypotheses tested, seventeen hypotheses were confirmed. Meanwhile, six hypotheses were not accepted, from the hypotheses that were not accepted there were results that were highlighted, namely that eco-label and halal-green awareness had no effect on purchase intention, but environmental knowledge had an effect on purchase intention. This is possible because there is still little public awareness and concern in selecting a product and its impact on the environment. And of the eight hypotheses with mediating variables, two hypotheses were found that could fully mediate. It is hoped that these findings can increase the intention to purchase local cosmetics that are halal and environmentally friendly, namely by better understanding consumer behavior, especially generation Z. The practical implications of this research are that cosmetic producers gain profits by entering the halal market and increasing market share by adding halal and environmentally friendly branding.